Proposals for Development Programme for the year 1975-76 Government of Gujarat - Planning Commission (Planning Commission, 1974)
The proposals formulated for the next year envisage an outlay of Rs. 165 crores. In addition, an outlay of about Rs. 15 crores is envisaged for undertaking additional works of development nature in the scarcity areas. While drawing the programmes, care has been taken to accord highest priority to the continuing projects. In view of the widespread scarcity prevailing in the State, labour intensive programmes have been given higher priority. The development works to be undertaken out of the additional outlay of Rs. 15 crores will also generate substantial employment. The actual distribution of additional outlay sector wise will depend on the demands of different categories of works in the different areas from time to time.
Government of Gujarat, General Administration Department (Planning)